The First Labour Hospital - Industrial Orthopaedic Society (Harlesden : Leveridge & Co.)
1923 1920s 4 pages The need for unity is just as strong on the social side of the worker's life as it is for the political and industrial. YOU can assist towards that unity which is so necessary by joining the FIRST LABOUR HOSPITAL which exists for the purpose of enabling the worker to be INDEPENDENT OF CHARITY in Hospital Treatment. There are thousands of workmen who have met with industrial accidents that have resulted in injured muscles and nerves, stiffened joints and contracted sinews. Such victims of industry are often doomed to spend the remainder of their lives on the industrial scrap heap, unless they can obtain specialised treatment of a very expensive character. By united effort it is possible to maintain and control a Hospital, the object of which is to bring within the reach of the worker the opportunity of recovery and re-establishment in the position previously occupied, instead of being condemned to industrial death. This is where the Labour Hospital steps in. The Hospital possesses the latest and most improved electrical massage appliances, a large fully competent massage staff, X-ray installation, etc. No charge is made for treatment beyond the entrance fee of 1s., and a contribution of 1d. per week. During 1923 there were 546 in-patients treated, 18,325 out-patient attendances were registered, 345 major and many minor operations were performed. Good work is being done which is of the utmost value to men who would otherwise be compelled to resign themselves to a future without prospects and without hope. The special features in this experiment in working class organization should commend it to everyone interested in the possibility of democratic control. Contributors are entitled to treatment, they are entitled to representation on the various Committees and thereby have the opportunity of expressing the point of view of the rank and file of the membership. 36/H24/16